Thermoresponsive NDP hydrogel embedded with MnO2 nanoparticles for postoperative antirecurrence therapy in pancreatic cancer - Zhongxu Yuan; Shuai Ma; Liang Yan; Man Xu; Dongquan Liu; Weicheng Wang; Bowen Han; Gan Chen; Zhengguang Wang (Scientific Reports)
Abstract Surgical resection remains a potentially curative treatment option for pancreatic cancer (PC). However, the high rate of local tumor recurrence and poor prognosis severely limit its therapeutic efficacy. In this study, we report an injectable thermosensitive hydrogel platform (designated as NDP@MnO2 hydrogel) that exhibits excellent biocompatibility, photothermal performance, and wet adhesion properties, specifically designed for precise post-operative therapy. This thermosensitive system innovatively combines shear-thinning injectability, dopamine-mediated tissue adhesion, and MnO2-enhanced photothermal ablation capabilities. By precisely targeting hyperthermia to the moist and irregular pancreatic resection margins during the sol-gel transition and subsequent exposure to an 808 nm laser, this approach can effectively and selectively eliminate residual tumor cells while minimizing collateral damage to adjacent healthy tissues. Notably, pre-clinical studies have demonstrated that this approach significantly reduces the locoregional recurrence rate in pancreatic cancer models, thereby offering a promising solution to the critical issue of postoperative recurrence.